Afro-Eccentricity - Hart, W. author. aut Link
X, 239 p.
Keywords: Afro-Eccentricity explores three overlapping stories of Black Religion: the Soul, Black Church, and Ancestor Narratives. Hart contends that these narratives dominate most accounts of Black Religion that, collectively, he calls the "Standard Narrative of Black Religion.".